Pengaruh Struktur Kepemilikan, Karakteristik Komite Audit dan Green Innovation terhadap ESG Disclosure dengan Ukuran Dewan Komisaris Sebagai Pemoderasi - Anjani, Made Delia Dwi; Yunirta, Gede Adi; Werastuti, Desak Nyoman Sri (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This study aims to provide empirical evidence on the impact of ownership structure, audit committee characteristics, and green innovation on ESG Disclosure, with board size as a moderating variable. A quantitative approach using panel data regression analysis was employed on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. Through purposive sampling, a total of 100 samples were obtained and analyzed using STATA software. The results show that ownership structure (coefficient = 0.0703; p = 0.498), audit committee characteristics (coefficient = 0.3470; p = 0.058), and green innovation (coefficient = 0.0278; p = 0.0514) have a positive but insignificant impact on ESG Disclosure. Additionally, board size strengthens the influence of ownership structure (coefficient = 0.0733; p = 0.114) and green innovation (coefficient = 0.0111; p = 0.642) on ESG Disclosure, but these effects are not significant. Conversely, board size weakens the impact of audit committee characteristics (coefficient = -0.2324; p = 0.020) on ESG Disclosure in a significant manner. Although the study shows that some variables have insignificant effects, it still provides insights into the challenges and potential for enhancing ESG Disclosure transparency in manufacturing companies listed on the IDX. This research enriches the literature on the factors influencing ESG Disclosure and the moderation of board size, while also promoting the strengthening of reporting standards and the adoption of sustainability practices, which can serve as a foundation for the development of policies supporting sustainable finance.